ANALISIS TINGKAT PEMAHAMAN MASYARAKAT TERHADAP PRODUK KEUANGAN Di DELI SERDANG (Studi kasus Tanjung Morawa) - Amena Kristiani Sitanggang; Wahyu Ario Pratomo (Ekonomi dan Keuangan, 2014)
The title of this research is the analysis of Societies Understanding Financial Products in Deli Serdang District of Tanjung Morawa. The purpose of this research is to identify and analyze the level of public understanding of the financial products offered by banks. These products include storage of funds, disbursement of funds and other services of the bank .The data used in this study is primary data and secondary data. The collecting of the primary data is done by giving the questionnaire to the people who live around Tanjung Morawa ,while the secondary data are obtained from books , literature, the Internet , and other media. The analytical method used is descriptive analysis using the computer program SPSS version 16.0.The result of this research indicate that the level of of public understanding of the financial products offered by banking is diverse. The highest level of understanding on storage products , while banking funds for the understanding of other products is still low . This is because customers only know the products that they use only.Keywords : Public Understanding , Banking